Amfory w ekspozycji Muzeum Archeologicznego w Murcji (Hiszpania) - Modrzewska-Pianetti, Iwona (Collectanea Philologica, 2022)
This article deals with ancient amphorae in the exhibition of the Archaeological Museum of Murcia (Spain). So far, the amphorae have only had inventory cards and there has been no typological-chronological study of them. Each of the 8 amphorae is a different type and purpose. These are finds from various locations in the Region of Murcia. The aim of the study is to supplement museum data and to show the Polish reader amphorae of local production and those imported to this region of Spain in the ancient period.